2008
DOI: 10.1136/bmj.39549.605602.be
|View full text |Cite
|
Sign up to set email alerts
|

Is there an epidemic of admissions for surgical treatment of dental abscesses in the UK?

Abstract: Steven J Thomas and colleagues think that recent changes in dental care provision have led to increased numbers of hospital admissions for dental abscess, and they suggest that access to routine and emergency dental care needs to be reviewed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 4 publications
6
49
0
Order By: Relevance
“…Their data are likely to underestimate DGA provision. They reported a rising trend in admissions which was consistent with an earlier study, 15 and postulated that this may be linked to two factors. Firstly, activity may have increased since all DGA now has to be administered in secondary care following the publication of A conscious decision.…”
Section: N B R I E F Opinion Opinionsupporting
confidence: 86%
“…Their data are likely to underestimate DGA provision. They reported a rising trend in admissions which was consistent with an earlier study, 15 and postulated that this may be linked to two factors. Firstly, activity may have increased since all DGA now has to be administered in secondary care following the publication of A conscious decision.…”
Section: N B R I E F Opinion Opinionsupporting
confidence: 86%
“…Changes in remuneration of dentists over the last decade has been reported to have caused a reduction in the proportion of NHS treatment carried out by general dentists. 3 The number of NHS general dental practitioners decreased after a further change in dentists' remuneration by introduction of the new contract in April 2006. The NHS information centre reported a reduction of 1,649 (8%) in NHS dental practitioners after introduction of the new contract in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The total number of hospital admissions and bed days as a result of drainage of a dental abscess in the UK has almost doubled between 1998-9 and 2005-6. 3 Severity of presentation has also increased. 2,[4][5][6][7] A lack of access to National Health Service (NHS) primary care dental services following changes in service provision and remuneration of dentists over the past ten years has been implicated as a root cause, particularly in areas of high treatment need.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The lowest survival of restorations was strongly and directly related to the shortest median frequency of attendances, due possibly to the higher occurrence of dental problems in the most frequent attendees. 4 A three-year study of dentate adults aged less than 35 years at baseline also found that similar percentages of 'dentally successful' people (56%) expected to retain teeth beyond the age of 65 …”
mentioning
confidence: 99%